FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GAGAL GINJAL KRONIK PADA PASIEN USIA < 45 TAHUN DI RUANG HEMODIALISA RSUD INDRAMAYU - Wayunah Wayunah; Neneng Ratnanengsih Puspitasari; Fatikhatul Jannah (JURNAL KESEHATAN INDRA HUSADA, 2017)
Chronic Renal Failure is a condition that decreasing kidney function, occurning progresive and irreversible. Many factors causes CRF in patiens aged < 45 years. Purpose of this study was to determine the factors associated with the occurrence of CRF in patiens age < 45 years.This research was conducted with case study approach. Samples selected with counsecutive technique sampling with 98 respondents. Data collection, this study using a questionnaire. The bivariae data analysis used in this study is the chi square test. The results is known factors associacted with in a diabetes mellitus of history factor (p value = 0,002) while factor unrelated chemical substances is a factor ( p value = 0,925), less intake of fluids factor (p value = 0,366), hypertension of history factor ( p value = 0,518) and history of obstruction of tract urinary factor (p value = 0,312). Conclusions in this research that there is a relationship between the factors of history of diabetes mellitus with chronic renal failure event in patients aged < 45 years. Suggestions in this study was shown to the nurse to increase public education about the prevention of the occurance of CRF.